Comparative public administration - Chandler, J. A., 1945- (Routledge, Taylor & Francis Group, 2014)
"This accessible introduction to the system of public administration uses a clear, country by country analysis to the contemporary system of public administration and management in a number of significant countries"--Resumé vydavatele
Keywords: management veřejné správy -- země světa; veřejná správa -- země světa; public administration management -- countries of the world; public administration -- countries of the world; srovnávací studie; comparative studies